Variation in Mangrove Growth Across Gradients of Species and Seeds in the Mangrove Restoration Area of Marga Sungsang, South Sumatra: Variasi Pertumbuhan Mangrove Lintas Gradien Jenis dan Benih di Kawasan Mangrove Restorasi Marga Sungsang, Sumatera Selatan - Apriyanto; Rujito Agus Suwignyo; Tengku Zia Ulqodry; Sarno; Riris Aryawati; Muhtadi; Herry Purnomo; Beni Okarda (Universitas Muhammadiyah Palembang, 2025)
Marga Sungsang has mangrove forests that have been degraded into plantations and require restoration activities. One restoration method that can be used is experimental multispecies planting. This study aims to determine the variation in mangrove growth across species and seed gradients. The data measured include environmental parameters, height growth per 3 months, and the number of branches and leaves. The results show that the water temperature ranges from 25.2 - 26.6 ° C and the soil pH ranges from 7.0 - 7.3 within the range that supports mangrove growth. The water pH value ranges from 12.1 - 14.3 and DO ranges from 3.5 - 4.1 mg / L both are outside the optimum range but mangroves can grow and adapt well to less than ideal conditions. Salinity ranges from 4.8 - 8.8 ppt is classified as low but still within the tolerance threshold. The total N content of 0.2% and total P of 13.3 - 41.8 ppm is in the low-moderate category and still meets initial nutritional needs. Rhizophora apiculata (RA) seedling has a high and significant growth rate, while Rhizophora apiculata (RA) and Bruguiera gymnorrhiza (BG) propagules show faster height growth in the early phase compared to seedling seeds. Rhizophora apiculata (RA) seedling and propagules produce almost the same number of leaves and branches at the end. These findings indicate that Rhizophora apiculata (RA) seedling and propagules are very suitable for planting in the mangrove restoration area of ​​Marga Sungsang Village.